Credit constraints and business performance: evidence from public lending in Colombia (2014)
Whether public lending to firms effectively eases credit constraints has been widely studied for very small businesses. The evidence documented for larger firms refers to lending that is significantly subsidized and targeted to these businesses, so the estimated positive effects may reflect poor allocation of public credit. This paper investigates the impact on its beneficiaries of a wide, untargeted and unsubsidized, lending program in Colombia. We use data on all non-micro manufacturing firms and all formal credit operations. After correcting for potential selection biases using econometric techniques, we find that Bancóldex loans increase firms' employment, purchases of inputs, investment, and output for small (but non-micro) firms, while large firms experience increases in variable inputs, but not on investment. While both short-term and long-term Bancóldex loans are found to have positive impacts on output, input demand and employment, only long-term loans increase investment. Moreover, short-term loans have a larger impact on input demand than long-term loans. Our findings also indicate that Bancóldex' beneficiaries end up with improved overall credit conditions after receiving Bancóldex credit: the amount of credit received goes up, the duration of the loans increases, and beneficiaries are able to establish credit relationships with more financial intermediaries. Though the interest rates go down, in this dimension the effect is small.